Acrogenospora (Acrogenosporaceae, Minutisphaerales) Appears to Be a Very Diverse Genus - Bao, Dan-Feng; McKenzie, Eric H. C.; Bhat, D. Jayarama; Hyde, Kevin D.; Luo, Zong-Long; Shen, Hong-Wei; Su, Hong-Yan (Frontiers in Microbiology, 2020)
During a study of diversity and taxonomy of lignicolous freshwater fungi in China, nine species of Acrogenospora were collected. Seven of these were new species and they are described, and illustrated. With morphology, additional evidence for the description of new species is provided by an analysis of combined LSU, SSU, TEF1α, and RPB2 sequence data. Acrogenospora subprolata and A. verrucispora were recollected and sequenced for the first time. The genus Acrogenospora is far more species rich than originally thought, with nine species found in a small area of Yunnan Province, in China.